Mullite-type Na0.67Al6O9.33 and a discussion of iota-alumina. Issue 12 (September 2020) - Lenz, Stephan; Schneider, Hartmut; Fischer, Reinhard X.
Abstract: Within the last sixty years, several authors stated that they have synthesized iota-alumina ( ι -Al2 O3 ), the hypothetical endmember of the mullite compositional series Al2 [Al2+2 x Si2−2 x ]O10- x with x  = 1. Iota-alumina is supposed to be a silica-free aluminate having a mullite-like X-ray diffraction pattern. However, no detailed information about its crystal structure has been provided. Therefore, we reproduced a typical sol-gel synthesis of ι -Al2 O3 and investigated the obtained material by X-ray powder diffraction (XRPD), EDS analysis, and thermal treatment. Our powder-diffraction diagrams conform to all published XRPD data of iota-alumina, but Rietveld and EDS analyses revealed that the putative ι -Al2 O3 actually is a Na-aluminate mullite (Na0.67 Al6 O9.33 ) with its pseudo-tetragonal metric: a  = 7.6778(4) Å, b  = 7.6767(3) Å, and c  = 2.9163(1) Å. For this reason, we assume that most of the phases designated as iota-alumina in the literature are in fact Na-aluminate mullites. Thus, the existence of ι -Al2 O3 with mullite-type structure is still a matter of debate.